Relationships among basal energy availability, nonnative predator success, and native fish declines in the upper Gila River Basin, NM, USA. - Whitney, James (Kansas State University, 2010)
Nonnative species represent a major threat to the continued persistence of native fishes globally, especially in the Colorado River Basin of western North America, where there are now more nonnative than native fishes. In the upper Gila River, a tributary of the Colorado, numerous nonnative fishes have established populations, and predation by these nonnatives has been linked to extirpation of native fishes under low-flow conditions at some locations. Historically, the upper Gila lacked a top piscivore, and it is unclear what mechanisms have allowed the establishment of nonnative piscivores and resultant extension in food chain length. To investigate the phenomenon of increased food chain length through nonnative introductions we explored the influence of autochthonous energy availability on nonnative predator abundance, food chain length, and abundance of other trophic levels. Predictions were that increased basal energy availability would lead to increased nonnative predator abundance and thus increased food chain length, based upon predictions from food web theory. Annual production and biomass of four trophic levels measured across six longitudinally-positioned sites were calculated between June 2008 and June 2009 to test these predictions. In addition, energy demand of trophic levels relative to energy supply was compared across sites using a quantitative food web approach, to evaluate energy limitation across trophic levels. Primary production was found to vary considerably across the upper Gila (1,677-16,276 kcal m-2 yr-1), but production and biomass of other trophic levels was not related to this gradient as predicted. In addition, food chain length demonstrated a marginally-significant negative relationship with primary production (R[superscript]2=0.42, d.f.=5, p=0.16), which was in contrast with predicted responses. These results suggest that energy availability does not appear to be a limiting factor to the production or biomass of consumers. The influence of other mechanisms on food chain length in the upper Gila River, in particular disturbance frequency and intensity, deserve further investigation.
Keywords: nonnative species; food chain length; secondary production; Gila River; primary production; quantitative food web; Agriculture, Fisheries and Aquaculture (0792); Biology, Ecology (0329); Biology, Limnology (0793)